Hybrid system for botany recognition/ Yew Kok Weng - Yew, Kok Weng (2005)
Hybrid System for Botany Recognition is a system that aims to be use as a botany expert system to aid students or other used of botanical field on plant identification. It contain a leaf recognition module where the system will be recognized a leaf template image and identify the features, fuzzy logic module that refine the recognition module's output data and an image database consist of the detail of species build based on Case Based Reasoning concept. This project proposal contains mainly the leaf recognition module. It contains a study of the current recognition technology, including both image processing field and the neural network field. It will also contain a brief review section. System analysis and design will detail the overall system including the software and hardware involve. A section of methodology will review the method used based on the principle of software engineering and will be applied throughout the phase to aid a smooth development.